Economic Analysis and Constraints of Traditional Processing of African Locust Bean in Kwara State, Nigeria - Solagberu Adisa, Rashid; Olushola Ayanshina, Simeon; Busola Olatinwo, Khadijat (Kasetsart Journal of Social Sciences, 2014)
The African locust bean (Parkia biglobosa) is mostly a wild-growing crop-tree whose fruit possesses widespread food and nonfood usefulness throughout West Africa. In Nigeria, the processing of African locust bean seeds (ALBS) into a soup condiment is a source of income among many rural households. Incidentally, ALBS processors are somewhat associated with poverty despite the widespread demand for the product. This study examined the economics and constraints of ALBS processing, with a view to identifying the interventional imperatives. The study was conducted in late 2011 in Kogi State, Nigeria—well known for the production of ALBS condiments. A systematic random sampling technique was used to select 139 respondents from a list of processors compiled with the assistance of leaders of the typically informal associations of ALBS processors. A structured questionnaire was used to collect data, while a reconnaissance survey of the study area was also conducted. A test-retest method was used to determine the reliability of the questionnaire, yielding a coefficient r value of .89, implying that the instrument was reliable. The results revealed that ALBS processing was dominated by middle-aged women, having little or no formal education, and mainly using labor-intensive traditional techniques. Cost-benefit analysis however revealed a relatively high profit margin. Regression analysis revealed that the cost of seeds, labor and water availability contributed most significantly to the output of ALBS processing among respondents. Major production constraints were ALB tree felling/burning, low technology application, and storage. The study recommended, inter alia, development of appropriate ALBS processing technology (such as a de-pulping machine) and virile extension and credit intervention.